Evaluation of Inclusive Education Services at Muhammadiyah 1 Kartasura Junior High School - Fadhia Ananda; Nurul Asma Khoiriyah; Anisa Meilawati; Annisah Safitri; Hana Ayu Safitri; Istanto Istanto (AL-ISHLAH: Jurnal Pendidikan, 2026)
Inclusive education aims to provide equitable learning opportunities for all students regardless of their abilities. Despite increasing policy support in Indonesia, limited evidence exists regarding the implementation of inclusive education in Islamic schools. This study evaluated the Muhjitos Inclusion Program at SMP Muhammadiyah 1 Kartasura as a model of inclusive education integrating academic excellence with humanistic and religious values.A qualitative case study was conducted using purposive sampling. Participants included the school principal, the inclusion program coordinator, Special Assistant Teachers (Guru Pendamping Khusus/GPK), subject teachers, and students with special needs. Data were collected through semi-structured interviews, classroom observations, and document analysis. The data were analyzed using the Miles and Huberman interactive model, while source and method triangulation and member checking were employed to ensure trustworthiness.Four major themes emerged: (1) adaptive implementation of inclusive learning through full inclusion and pull-out instruction; (2) the pivotal role of GPK in differentiated instruction and emotional support; (3) a collaborative ecosystem involving teachers, parents, and psychologists; and (4) students' holistic development encompassing academic, social, emotional, and character growth. The findings indicate that the program has been effectively implemented for three years, primarily serving students with mild disabilities through individualized support and collaborative educational practices.The study proposes an Inclusive Excellence Model comprising adaptive instructional flexibility, collaborative ecosystem synergy, and the integration of humanistic-spiritual values. The findings suggest that inclusive education and academic excellence can be achieved simultaneously through adaptive pedagogy, sustained stakeholder collaboration, and institutional commitment to educational equity, offering practical implications for the development of inclusive education in Islamic schools.